Developing a procurement framework for the Malaysian hospitality industry: a preliminary study / Siti Zalipah Ibrahim... [et al.] - Ibrahim, Siti Zalipah; Lahap, Johanudin; Nazlan, Nadia Hanin; Ariffin, Hashim Fadzil; Mohd Said, Noraslinda (Universiti Teknologi Mara Cawangan Pulau Pinang, 2020)
Businesses are made up of many sub-structure of activities. One particular activity that demands high attention is procurement. In the hospitality industry, the procurement department plays a major role in ensuring supply of raw material and goods are planned, purchased, distributed, and consumed efficiently. An influx of activities such as requisition, acquisition, and quality check is done in this department. In estimating the total cost of acquiring goods and services, it is important for organizations to identify unit costs and other costs associated with operations and maintenance that occurs during purchasing and conserving of goods. Recent studies have reported the usage of an Electronic Procurement System (EPS) that replaces the conventional procurement system typically used in Hotels. This paper aims to explore the current practice, effectiveness and efficiency of the procurement systems used in Malaysian hotels through in-depth interviews. Findings of this study will assist hospitality businesses to analyze their procurement activities and develop proper strategies that enables them to reduce costs, increase efficiency, and most importantly, improve their bottom line.